Book Reviews - Susskind, Jacob L.; Fischer, Robert; Luehrs, Robert B.; McCarthy, Joseph M.; Micciche, Pasquale E.; Lowry, Bullitt; Frey, Linda; Steinson, Barbara J.; King, Kay; Quinlivan, Mary E.; et al. (Teaching History: A Journal of Methods, 2020)
J. M. MacKenzie. The Partition of Africa, 1880-1900. London and New York: Methuen, 1983. Pp. x, 48. Paper, 2.95. Review by Leslie C. Duly of Bemidji State University. C. Joseph Pusateri. A History of American Business. Arlington Heights, Illinois: Harlan Davidson, Inc., 1984. Pp. xii, 347. Cloth, 25.95; Paper, 15.95. Review by Paul H. Tedesco of Northeastern University. Russell F. Weigley. History of the United States Army. Enlarged edition. Bloomington: Indiana University Press, 1984. Pp. vi, 730. Paper, 10.95. Review by Calvin L. Christman of Cedar Valley College. Jonathan H. Turner, Royce Singleton, Jr., and David Musick. Oppression: A Socio-History of Black-White Relations in America. Chicago: Nelson-Hall, 1984. Cloth, 24.95; Paper, 11.95. Review by Thomas F. Armstrong of Georgia College. H. Warren Button and Eugene F. Provenzo, Jr. History of Education and Culture in America. Englewood Cliffs, New Jersey: Prentice-Hall, Inc., 1983. Pp. xvii, 370. Cloth, 20.95. Review by Peter J. Harder. Vice President, Applied Economics, Junior Achievement Inc. David Stick. Roanoke Island: The Beginnings of English America. Chapel Hill and London: University of North Carolina Press, 1983. Pp. xiv, 266. Cloth, 14.95; Paper, 5.95. Review by Mary E. Quinlivan of the University of Texas of the Permian Basin. John B. Boles. Black Southerners 1619-1869. Lexington: The University Press of Kentucky, 1983. Pp. ix, 244. Cloth, 24.00; Paper, 9.00. Review by Kay King of Mountain View College. Elaine Tyler May. Great Expectations: Marriage and Divorce in Post-Victorian America. Chicago: University of Chicago Press, 1980. Pp. viii, 200. Cloth, 15.00; Paper, 6.95. Review by Barbara J. Steinson of DePauw University. Derek McKay and H. M. Scott. The Rise of the Great Powers, 1648-1815. London: Longman, 1983. Pp. 368. Paper, 13.95. Review by Linda Frey of the University of Montana. Jack S. Levy. War in the Modern Great Power System, 1495-1975. Lexington: The University Press of Kentucky, 1983. Pp. xiv, 215. Cloth, 24.00. Review by Bullitt Lowry of North Texas State University. Lionel Kochan and Richard Abraham. The Making of Modern Russia. Second Edition. New York: Penguin Books, 1983. Pp. 544. Paper, 7.95. Review by Pasquale E. Micciche of Fitchburg State College. D. C. B. Lieven. Russia and the Origins of the First World War. New York: St. Martin’s Press, 1983. Pp. 213. Cloth, 25.00. Review by Joseph M. McCarthy of Suffolk University. John F. V. Kieger. France and the Origins of the First World War. New York: St. Martin’s Press, 1983. Pp. vii, 201. Cloth, 25.00. Review by Robert B. Luehrs of Fort Hays State University. E. Bradford Burns. The Poverty of Progress: Latin Amerca in the Nineteenth Century. Berkeley: University of California Press, 1980. Pp. 185. Paper, 6.95. Review by Robert Fischer of the Southern Technical Institute. Anthony Seldon and Joanna Pappworth. By Word of Mouth: Elite Oral History. London and New York: Methuen, 1983. Pp. xi, 258. Cloth, 25.00; Paper, 12.95. Review by Jacob L. Susskind of the Pennsylvania State University, The Capitol Campus.